Iatrogenic Right Ventricular Laceration: Delayed Presentation after Abdominal Surgery - Neri, Eugenio (2000)
A 69-year-old man presented at our emergency department in marginal hemodynamic condition due to hemorrhagic shock and cardiac tamponade. Two months earlier, he had undergone total gastrectomy and left lobe hepatectomy for inva s i ve gastric cancer. Delayed iatrogenic laceration of the right ventricle, consequent to the abdominal procedure, was the uncommon cause of the massive hemopericardium. To our knowledge, this is only the 2nd case in the literature of a cardiac laceration after abdominal surgery.